Cardiac disease pattern amongst patients presenting to the echocardiography unit in a rural teaching hospital- A cross sectional study - Gurung, Dhiraj; Gurung, Uma (Journal of Karnali Academy of Health Sciences, 2021)
Background- Cardiac disease is the second most common non-communicable disease in Nepal but we do not yet have data for the upper Karnali region. This paper assesses the prevalence of various types of cardiac diseases in the sole tertiary level hospital serving the upper Karnali region.Methods- This is a single center, descriptive, cross-sectional study of one year duration from July 2019 to August 2020 involving a total of 284 patients who underwent echocardiography in karnali academy of health sciences. Data on patient variable such as age, sex and diagnosis were obtained from hospital medical records.Results- Out of a total of 284 patients, Cor-pulmonale was seen in 90 (31.6%) patients, Diastolic dysfunction in 52(18.3%) patients, Valvular heart disease in 21(7.3%) patients, Cardiomyopathy in 11 (3.8%) patients, Myocardial infarction in 9(3.1%) patients and congenital heart disease in 7(2.4%) patients.Conclusions- Cor-pulmonale and diastolic dysfunction were the top two common cardiac disease in our study area. Community based study of cardiac disease and screening of rheumatic heart disease is recommended due to its low prevalence in our study area.